Minimizing The Phenomena of Reflection Cracks. A Review - Jasim, Sameer A.; Al-Mosawe, Hasan Mosa; Nassar, Ahmed I. M. (Al-Nahrain Journal for Engineering Sciences, 2025)
Reflective cracking is a serious issue that Adversely influences the performance and longevity of asphalt overlays over deteriorated pavements. This review Looks for the Technologies which used to reduce the reflection cracks propagation by insert a new Strategies and different design materials. This research dealt with many treatments such as: increasing the layer thickness of Hot Mix Asphalt (HMA), creating modified asphalt by adding polymers to asphalt, rubberizing asphalt, carbon black, sulfur and other different materials. Geosynthetic materials were studied and analyzed to evaluate their ability to increase the layer tensile strength and minimize the effect of reflection cracks such as geotextiles, geogrids, and Stress Absorbing Membrane Interlayers (SAMI). The research shows that the increasing of overlay asphalt layer thickness leads to durability development. On the other hand, using developed materials like Polymer-Modified Asphalt and Stress Absorbing Membrane Interlayers (SAMI) Strategies leads to increasing the service life of the repaired pavement. The conclusion indicated that the development of overlay asphalt layer thickness and layer reinforcement and applying advanced environmental systems can be improving the pavement performance. These Strategies can produce a perfect solution to prevent or reduce the reflection cracks in rigid and flexible pavement.